2014
DOI: 10.1007/s10758-014-9238-0
|View full text |Cite
|
Sign up to set email alerts
|

Flipped Classroom Versus Traditional Textbook Instruction: Assessing Accuracy and Mental Effort at Different Levels of Mathematical Complexity

Abstract: Flipped classrooms are an instructional technology trend mostly incorporated in higher education settings, with growing prominence in high school and middle school (Tucker in Leveraging the power of technology to create student-centered classrooms. Corwin, Thousand Oaks, 2012). Flipped classrooms are meant to effectively combine traditional and online education by utilizing both in and out-of-class time. Despite positively reported implications of the flipped classroom instructional strategy, there is a deep s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(60 citation statements)
references
References 45 publications
1
47
0
12
Order By: Relevance
“…Also, similar variances were also detected in in-class assessments and the lab taken during the course. Previously published research [15,16,34] regarding the students' performance indicated that there is not enough evidence to support assertions of the flipped-classroom model benefits in the students' performance. Christiansen [35] shows similar conclusions described in a more limited study and a much smaller class group.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Also, similar variances were also detected in in-class assessments and the lab taken during the course. Previously published research [15,16,34] regarding the students' performance indicated that there is not enough evidence to support assertions of the flipped-classroom model benefits in the students' performance. Christiansen [35] shows similar conclusions described in a more limited study and a much smaller class group.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, this research denotes that more teaching materials and resources were used when a flipped-classroom was followed. Comparable results were explained in a mathematics course [15,16] where the flipped-classroom model improved the grades of students. Also, this work suggests that the flipped-classroom model demonstrated its higher accuracy, especially on moderate complexity items.…”
Section: Introductionmentioning
confidence: 86%
“…Previous studies of flipped class teaching have obtained promising results for various academic outcomes including enhancement of subject‐based performance, language acquisition, critical thinking and information literacy (Arnold‐Garza, ; Correa, ; Fulton, ; Kong, ; Mattis, ; Schultz et al ., ; Siegle, ). However, these studies ignore the fundamental purpose of education, that is, to develop “self‐learning ability and an inquisitive mind” (Hong Kong Education Bureau, ).…”
Section: Introductionmentioning
confidence: 99%
“…So, in-class time is used to work in more student-centered learning activities, thereby making interactive courses (Moraros et al 2015) or delivering justin-time lectures to address specific questions. A flipped classroom setting could also be understood as a combination of both traditional and online education by employing in-and out-of-class time, accomplishing more efficient learning opportunities (Young 2002;Mattis 2014). A main character of this instruction methodology is that students have more responsibility in the learning process (O'Flaherty and Phillips 2015).…”
Section: Introductionmentioning
confidence: 99%